Cover Picture: Electrochemical Lossy Mode Resonance‐based Fiber Optic Sensing for Electroactive Species (Electroanalysis 3/2023). Issue 3 (13th March 2023) - Okazaki, Takuya; Yoshioka, Masaki; Orii, Tatsuya; Taguchi, Akira; Kuramitz, Hideki; Watanabe, Tomoaki
Abstract : The cover image is based on the Research Article Electrochemical Lossy Mode Resonance‐based Fiber Optic Sensing for Electroactive Species by Takuya Okazaki et al., DOI: 10.1002/elan.202200089 .